Factors Affecting the Utilization of Medical Check Up at the Putri Hijau Level II Hospital - Putri Junita Sembiring; Aisyah Simanjorang; Nur Aini (Journal La Medihealtico, 2021)
The purpose of this research is to investigate the variables that affect the use of medical services. At the Putri Hijau Level II Hospital, you may get checked out. It was decided to employ a kuantitatif research design with a cross sectional design for this particular investigation. Patients who came in for a medical check-up at the Putri Hijau Level II Hospital were included in the research study. According to the results of the first survey, the total number of patients who had medical examinations in 2019 was 2135 individuals. We needed to look at 100 different individuals for our experiment. The chi square test and multiple linear regression were the statistical tests that were used. The results of the chi square test study revealed that the variable service quality (reliability p-value = 0,000, responsiveness p-value = 0,000, assurance p-value = 0,036, empathy p-value = 0,003, physical evidence p-value = 0,026) obtained a p-value less than 0.05, the variable facility p-value = 0.000, the variable rate / price p-value = 0.000, and the variable patient perception obtained a p-value Patient views of the use of Medical Check Up services are associated with service quality (reliability, responsiveness, assurance, empathy, physical evidence) as well as medical facilities, rates / pricing and patient perceptions of the usage of Medical Check Up services (p-value = 0.039 0.05). Using multivariate analysis, it was discovered that one of the variables in this research, the Facility variable, had the most influence on the outcome.